Класифікація засобів та методів семантичного пошуку в Web - Рогушина, Ю.В. (Проблеми програмування, 2017)
Розглянуто проблеми, пов’язані з удосконаленням пошуку інформації у відкритому середовищі, обґрунтована потреба в його семантизації. Проаналізовано сучасний стан та перспективи розвитку систем семантичного пошуку, орієнтованих на обробку інформаційних ресурсів Web, розглянуто критерії класифікації таких систем. В цьому аналізі значна увага приділяється використанню у семантичному пошуку онтологій, що містять знання щодо предметної області пошуку та користувача, для якого виконується пошук. На основі аналізу властивостей існуючих систем семантичного пошуку з точки зору цих критеріїв виділені області подальшого вдосконалення цих систем, запропоновано їх реалізацію у системі семантичного пошуку “МАІПС”. Рассмотрены проблемы, связанные с усовершенствованием поиска информации в открытой среде, обоснована потребность в ее семантизации. Проанализировано современное состояние и перспективы развития систем семантического поиска, ориентированных на обработку информационных ресурсов Web, рассмотрены критерии классификации таких систем. В этом анализе значительное внимание отводится использованию в семантическом поиске онтологий, которые содержат знания относительно предметной области поиска и относительно пользователя, для которого выполняется поиск. На основе анализа свойств существующих систем семантического поиска с точки зрения этих критериев выделенные области дальнейшего усовершенствования этих систем, предложена их реализация в системе семантического поиска "МАИПС". Problems associated with the improve ment of information retrieval for open environment are considered and the need for it’s semantization is grounded. Thecurrent state and prospects of development of semantic search engines that are focused on the Web information resources processing are analysed, the criteria for the classification of such systems are reviewed. In this analysis the significant attention is paid to the semantic search use of ontologies that contain knowledge about the subject area and the search users. The sources of ontological knowledge and methods of their processing for the improvement of the search procedures are considered. Examples of semantic search systems that use structured query languages (eg, SPARQL), lists of keywords and queries in natural language are proposed. Such criteria for the classification of semantic search engines like architecture, coupling, transparency, user context, modification requests, ontology structure, etc. are considered. Different ways of support of semantic and otology based modification of user queries that improve the completeness and accuracy of the search are analyzed. On base of analysis of the properties of existing semantic search engines in terms of these criteria, the areas for further improvement of these systems are selected: the development of metasearch systems, semantic modification of user requests, the determination of an user-acceptable transparency level of the search procedures, flexibility of domain knowledge management tools, increasing productivity and scalability.